Parasite-based confirmation of malaria with rapid diagnostic tests: Challenges and Advantages - Okangba, Chika Celen (Pure and Applied Science Advances, 2019)
The key to effective case management of malaria is prompt and accurate diagnosis of malaria which is necessary to prevent morbidity and mortality. Accurate and practical malaria diagnostic such as immunochromatographic rapid diagnostic test can avert unnecessary treatments and save lives. Malaria presents a diagnostic challenge in most tropical countries. The urgency and importance of obtaining results quickly from the examination of blood samples from patient with suspected malaria is possible with the introduction of rapid malaria diagnostic test. Rapid diagnostic tests are useful in guiding therapeutic intervention, can be accessible to rural and urban populations, easy to perform and to interpret, affordable, requires no sophicated equipment and prompt treatment of malaria. The use of rapid diagnostic test in the case management of malaria has a lot of challenges which includes: persistent of histidine rich protein 2 in circulation after therapy and parasite death, effect of genetic diversity, lack of quality control on microscopy examination, poor transportation and storage condition, poor regulatory mechanism, lot-to-lot variation, parasite density and lack of extensive training prior to the use of rapid diagnostic test and supervision.